Android-Based Interactive Multimedia Development For Enhancing Creative Thinking In High School Civic Education - Rike Erlande; Kokom Komalasari; Rahmat; Iim Siti Masyitoh; Markus Matulessy (Universitas Pendidikan Ganesha, 2026)
This study aims to describe the development of Android-based interactive multimedia in Civic Education (PPKn) to enhance students' creative thinking. The research employs the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design model. The study subjects are 10th-grade students and teachers from SMA Islam Azzahrah Palembang, SMA Negeri 13 Palembang, and SMA Negeri Sumatera Selatan. The research sample, chosen using purposive sampling, includes 10th-grade IPA 1 and IPA 3 students from SMA Islam Azzahrah to assess the effectiveness of the learning media. The research instruments include observation, interviews, questionnaires, and tests. The results indicate that (1) the implementation of learning media in SMA Islam Azzahrah, SMA Negeri 13 Palembang, and SMA Negeri Sumatera Selatan is not yet optimal in using Android-based digital media, and there is a low level of creative thinking in PPKn lessons; (2) the Android-based interactive multimedia developed for PPKn learning is categorized as valid based on expert validation results from media experts, subject matter experts, and students, with very practical results; and (3) Android-based interactive multimedia significantly influences the enhancement of creative thinking. The implementation of Android-based interactive multimedia in Civic Education, particularly on the topic of